Implementing Problem-Based Learning with Patchwork-Based Presentation Media to Enhance Student’s Speaking Performance in Procedure Text - Fika Rokaya; Seful Bahri (Universitas Islam Negeri Palopo, 2025)
In English language learning, students’ speaking performance remains a challenge, particularly in producing procedural texts. The purpose of this study was to examine the effectiveness of implementing Problem-Based Learning integrated with Patchwork-Based Presentation Media in enhancing students’ speaking performance in procedure texts. This study was conducted with XI DPB (Desain dan Produksi Busana) 1 students at SMK Negeri 1 Pringapus using a quasi-experimental one-group pre-test–post-test design with a qualitative follow-up. The data were collected through speaking performance tests, classroom observations, and student interviews. The findings show two main results. First, the implementation of Problem-Based Learning supported by Patchwork-Based Presentation Media resulted in a statistically significant improvement in students’ speaking performance, as indicated by higher post-test scores and a significant p-value (p < 0.05). Second, the learning approach encouraged students' active participation, developed their problem-solving skills, increased their confidence, and motivated them to engage in speaking activities. The integration of problem-based tasks and patchwork-based presentation media also helped students organize procedural sequences, use appropriate vocabulary and grammatical structures, and improve fluency and clarity in delivering procedure texts. Overall, the study concludes that implementing Problem-Based Learning with Patchwork-Based Presentation Media is an effective and student-centered approach to enhancing students’ speaking performance in procedure texts, particularly in vocational high school contexts.